Activation of the Fas receptor on lung eosinophils leads to apoptosis and the resolution of eosinophilic inflammation of the airways. - Tsuyuki, S (1995)
While considerable progress has been made in understanding the events by which eosinophils accumulate in various pathophysiological conditions, the mechanisms controlling the resolution of eosinophilic inflammation are poorly understood. In the present study, we demonstrate that lung eosinophils obtained by bronchoalveolar lavage (BAL) after aerosol allergen provocation of immunized mice expressed the Fas receptor. Stimulation of purified eosinophils in vitro with a monoclonal anti-Fas mAb (1 ng-1 microg/ml) induced a dose/time dependent loss of cell viability from 24-72 h. Measurement of DNA fragmentation with propidium iodide confirmed that anti-Fas induced eosinophil death by apoptosis. While incubation with IL-3, IL-5, or GM-CSF prevented spontaneous apoptosis, these factors failed to prevent anti-Fas induced apoptosis. Administration of anti-Fas mAb to the lungs after the induction of a lung eosinophilia increased the number of peroxidase positive macrophages in BAL fluid 4-12 h later which was followed by a marked reduction in the number of eosinophils in the airways. Importantly, Fas-mediated resolution of eosinophilic inflammation occurred in the absence of any overt secondary inflammatory changes in the lungs. We speculate that defects in this pathway may at least in part explain the chronic eosinophilic inflammation often observed in the lungs of asthmatic individuals.